Idiopathic lymphoplasmacellular mucositis of the vulva in a patient with partial interferon-γ receptor 1 deficiency - Kuan-Yu Chen; Tseng-Tong Kuo; Ya-Ching Chang; Rosaline Chung-Yee Hui; Ya-Hui Chuang (Wolters Kluwer Medknow Publications, 2019)
We report a case of idiopathic lymphoplasmacellular mucositis (ILPM) of the vulva in a 48-year-old woman with partial interferon-γ receptor 1 (IFN-γR1) deficiency. The lesion had an unusual ulcerovegetative presentation. Remarkable response was observed with oral and topical steroids in the first 3 weeks. However, the lesion recurred after tapering oral steroids and continuous low-dose oral steroids were required to suppress recurrence. To the best of our knowledge, this is the first case report of ILPM in a patient with partial IFN-γR1 deficiency. ILPM should be included in the differential diagnosis of persistent vulvar ulcerovegetative lesions.